2003
DOI: 10.1038/sj.tpj.6500221
|View full text |Cite
|
Sign up to set email alerts
|

A Gilbert's syndrome UGT1A1 variant confers susceptibility to tranilast-induced hyperbilirubinemia

Abstract: Tranilast (N-(3 0 4 0 -demethoxycinnamoyl)-anthranilic acid (N-5)) is an investigational drug for the prevention of restenosis following percutaneous transluminal coronary revascularization. An increase in bilirubin levels was observed in 12% of patients upon administration of tranilast in a phase III clinical trial. To identify the potential genetic factors that may account for the drug-induced hyperbilirubinemia, we examined polymorphisms in the uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…62 For the agent tranilast, a phase III clinical trial failed to demonstrate significant reduction of restenosis after coronary artery stenting, 63 but with an appropriately powered, retrospective, genome-wide analysis, UGT1A1*28 was identified as a predictor of a common toxicity of tranilast -hyperbilirubinemia. 27,28,64 As early studies suggested this specific dinucleotide repeat to be important to clinical phenotypes, its variability among primates and human populations has been extensively characterized. 65,66 However, other sites within the UGT1A locus may modify UGT1A1*28-associated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 For the agent tranilast, a phase III clinical trial failed to demonstrate significant reduction of restenosis after coronary artery stenting, 63 but with an appropriately powered, retrospective, genome-wide analysis, UGT1A1*28 was identified as a predictor of a common toxicity of tranilast -hyperbilirubinemia. 27,28,64 As early studies suggested this specific dinucleotide repeat to be important to clinical phenotypes, its variability among primates and human populations has been extensively characterized. 65,66 However, other sites within the UGT1A locus may modify UGT1A1*28-associated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…27 A staged, genome-wide analysis has associated three single nucleotide polymorphisms (SNPs) of the UGT1A locus with this toxicity. 28 Although it is reasonable to assume that the association between hyperbilirubinemia and these pharmacologic agents is based on genetic variation at UGT1A1, for other metabolic/ toxicologic phenotypes of UGT1A, the overlapping tissue distributions and substrate affinities of enzymes encoded by this locus may complicate interpretation of single genotype or single exon-haplotype association studies.…”
Section: Introductionmentioning
confidence: 99%
“…The UGT1A1 genetic variant TA7 is known to cause reduced expression of UGT1A1 (Bosma et al, 1995), and the TA7/TA7 (*28/*28) genotype predisposes individuals to Gilbert's syndrome, a benign form of episodic jaundice (Bosma et al, 1995;Raijmakers et al, 2000). This UGT1A1 TA-repeat polymorphism has also been reported to be associated with hyperbilirubinemia induced by several drugs, such as tranilast, nilotinib, and indinavir (Zucker et al, 2001;Danoff et al, 2004;Singer et al, 2007). Pazopanib is a potent inhibitor of UGT1A1 activity in vitro, with an IC 50 of 1.2 mM.…”
Section: Discussionmentioning
confidence: 99%
“…6 The (TA) 7 allele, whether homozygous or heterozygous, confers a increased risk of leukopenia and diarrhea during irinotecan treatment. 7,8 The homozygous (TA) 7 /(TA) 7 genotype (henceforth referred to as '7/7') has also been associated with increased risk of hyperbilirubinemia during treatment with the anti-restenosis drug tranilast 9 and the anti-HIV treatment indinavir. 10 Nilotinib is a novel inhibitor of the BCR-ABL chimeric kinase that causes chronic myeloid leukemia (CML).…”
Section: Introductionmentioning
confidence: 99%